The concept of liability in civil law - Слома, Валентина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article explores the concept of liability in civil law. All participants of civilian turnover, no matter whether they are entities or individuals, enter the property relationships and personal non-property relations. These relations are indicated by the term "legal obligation". However, the concept of commitment is not defined in the law and in legal literature. In Roman law liability was considered as a subjective legal situation based on a personal connection between specific members of civil circulation (parties), which is based in the formal opportunity for one of them (the creditor) to request from another one (debtor) the certain behavior (provision) in their favor. With the development of economic turnover the liability was its main form. If the main condition of the liability was the offense in ancient times, then the ratio had been changed: the obligations arising from tort became lost among a large number of liabilities (obligations) arising from contracts. Central Committee of the USSR in 1922 in the art. 107 provided that because of the obligation, one person (the lender) has the right to require from another person (the debtor) certain actions, including the transferring the goods or payment of money or refraining from action. It should be noted that this article only provides for the right of the lender, but does not mention the obligation of the debtor. Central Committee of the USSR in 1963 (Art. 151) contained more expanded definition of liability provided both a right of the creditor and the debtor’s obligation. In civil law there are two concepts of civil liability. The first one includes all legal relations between the parties arising under the bilateral agreement. The second one shares these links into two obligations, all of which have only one creditor and one debtor. According to the Art. 509 of CC Ukraine liability is a commitment in which one party (the debtor) is obliged to act in favor of the other party (the creditor) a certain action (to transfer the property, perform the work, provide services, pay money, etc.) or to refrain from certain actions, and the creditor may require the debtor to perform his duty.